2015
DOI: 10.9710/kjm.2015.31.4.263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Temperature Condition on Growth and Survival of Juvenile Geoduck (Panopea japonica A. Adams, 1850)

Abstract: This study was performed to determine the effect of water temperature condition on survival rate and growth of juvenile geoduck (Panopea japonica). Panopea japonica juveniles were bred for 6 weeks at 12, 15, 18, 21, 24 and 27℃ on incubator. Juveniles median lethal times (LT50) were 29 hours in 27℃, 14.5 day in 24℃, 37.4 day in 21℃. Survival rate of water temperature 12, 15 and 18℃ showed a high survival rate in 95.0%, 95.0% and 93.3% at 6 weeks. As a result of culturing for 6 weeks at 12, 15, 18, 21 and 24℃, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…The developmental rate of P. zelandica in the present study also increased with increasing temperature. This is in agreement with several other studies on marine invertebrates that have shown that higher temperatures tend to enhance the rate of cleavage of the developing embryos up to a certain point (Chen & Chen, 1992;Dehnel & Kong, 1979;Delorme & Sewell, 2013;Dos Santos & Nascimento, 1985;Huo et al, 2017;Lee & Rho, 1997;Nam et al, 2015). The developmental rates at recorded temperatures in the present study are similar to those observed by Le et al (2018) on P. zelandica (at 15°C) and by Lee and Rho (1997) on P. japonica (at 11, 14, and 17°C).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The developmental rate of P. zelandica in the present study also increased with increasing temperature. This is in agreement with several other studies on marine invertebrates that have shown that higher temperatures tend to enhance the rate of cleavage of the developing embryos up to a certain point (Chen & Chen, 1992;Dehnel & Kong, 1979;Delorme & Sewell, 2013;Dos Santos & Nascimento, 1985;Huo et al, 2017;Lee & Rho, 1997;Nam et al, 2015). The developmental rates at recorded temperatures in the present study are similar to those observed by Le et al (2018) on P. zelandica (at 15°C) and by Lee and Rho (1997) on P. japonica (at 11, 14, and 17°C).…”
Section: Discussionsupporting
confidence: 93%
“…The developmental rates at recorded temperatures in the present study are similar to those observed by Le et al () on P. zelandica (at 15°C) and by Lee and Rho () on P. japonica (at 11, 14, and 17°C). Nam et al () further shortened the incubation time of P. japonica to reach D‐veliger larvae to 27 hr by maintaining the embryos at 19°C. While it may be beneficial for hatcheries to maximize the developmental rate, the thermal threshold for normal development should not be exceeded (Delorme & Sewell, ; Dos Santos & Nascimento, ; Huo et al, ; Parker, Ross, & O’Connor, ; Parker et al, ), as the percentage of abnormalities appears to greatly increase with increasing temperatures.…”
Section: Discussionmentioning
confidence: 99%